Pengembangan Strategi Pemasaran Hotel Irene Kecamatan Amahai Kabupaten Maluku Tengah - Richard A. de Fretes; Billy J. Camerling (ARIKA, 2024)
The adequate parking area, number of rooms available at varying prices with inadequate facilities plus the emergence of new competitors/new hotels with more modern room interior designs with varying prices and better service facilities make Hotel Irene a must can compete in the hotel business. By still using virtual glasses analysis to promote hotel marketing, it has not been able to increase the number of visits/customer service at the Irene hotel. This research aims to analyze the marketing of the Irene Hotel, Amahai subdistrict, Central Maluku district through identifying internal and external factors. The data analysis method used is descriptive qualitative and quantitative with data collection techniques through observation, interviews, questionnaires and literature study. Analysis of the IFE and EFE matrices produces 17 factors with weights of 1.008 and 1.713 respectively so that the current position of developing the marketing strategy for the Irene hotel is in cell IX with the main strategies namely divestment, conglomerate diversification strategy and liquidation strategy. Data processing using SWOT analysis produces 4 alternative strategies that are formulated for developing marketing strategies for the Irene hotel.